Deep Brain Stimulation for the Treatment of Resistant Depression: Systematic Review of the Literature - Julião, Ícaro Elias Gualberto Santos; Santana, Diego Ferreira; Silva, Ledismar José da (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Depression is the leading cause of disability worldwide, and it is related to high suicide rates. Furthermore, a great number of patients do not respond to any of the available treatments. Deep brain stimulation (DBS), a versatile technology with expanding indications, is considered a potential treatment for resistant depression. However, in over 10 years of clinical research, its efficacy has not been completely proven. Although new trials using DBS for treatment-resistant depression keep emerging, two of the three Level I evidence-based studies recently conducted have not provided conclusive data. Methodological limitations and major biases have compromised the obtention of clearer results. In this systematic review of the literature, we intend to critically assess the clinical trials performed in this field.
Keywords: deep brain stimulation; treatment-resistant depression; refractory depression